Women and Confucian cultures in premodern China, Korea, and Japan - Ko, Dorothy, 1957-; Haboush, JaHyun Kim; Piggott, Joan R. (Berkeley : University of California Press, 2003)
Representing an unprecedented collaboration among international scholars from Asia, Europe, and the United States, this volume rewrites the history of East Asia by rethinking the contentious relationship between Confucianism and women. The authors discuss the absence of women in the Confucian canonical tradition and examine the presence of women in politics, family, education, and art in premodern China, Korea, and Japan.
pt. 1. Scripts of male dominance. The patriarchal family paradigm in eighth-century Japan / Hiroko Sekiguchi ; The last classical female sovereign: Kōken-Shōtoku Tennō / Joan R. Piggott ; Representation of females in twelfth-century Korean historiography / Hai-soon Lee -- The presence and absence of female musicians and music in China / Joseph S.C. Lam -- pt. 2. Propagating Confucian virtues. Woomen and the transmission of Confucian culture in Song China / Jian Zang ; Propagating female virtues in Chosŏn Korea / Martina Deuchler ; State indoctrination of filial piety in Tokugawa Japan: sons and daughters in the Official records of filial piety / Noriko Sugano -- pt. 3. Female education in practice. Norms and texts for women's education in Tokugawa Japan / Martha C. Tocco ; Competing claims on womanly virtue in late imperial China / Fangqin Du and Susan Mann -- pt. 4. Corporeal and textual expressions of female subjectivity. Discipline and transformation: body and practice in the lives of Daoist holy women of Tang China / Suzanne E. Cahill ; Versions and subversions: patriarchy and polygamy in Korean narratives / JaHyan Kim Haboush.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Women -- China -- History; Women -- Japan -- History; Women -- Korea -- History; Confucianism -- Social aspects; Women in Confucianism -- China; Women in Confucianism -- Japan; Women in Confucianism -- Korea; Femmes -- Chine -- Histoire; Femmes -- Japon -- Histoire; Femmes -- Corée -- Histoire; Confucianisme -- Aspect social; Femmes dans le confucianisme -- Chine; Femmes dans le confucianisme -- Japon; Femmes dans le confucianisme -- Corée.; SOCIAL SCIENCE -- Women's Studies; HISTORY -- Asia -- General; Women in Confucianism; Confucianism -- Social aspects; Women; China; Japan; Korea; Konfuzianismus; Frau; China; Japan; Korea; Vrouwen; Confucianisme; Geschichte; History; Aufsatzsammlung